The Sisters of Nazareth convent - Dark, K. R. (Ken R.), author.
1 online resource.
Keywords: "This book transforms archaeological knowledge of Nazareth by publishing over 80 years of archaeological work at the Sisters of Nazareth convent, including a detailed re-investigation in the early twenty-first century under the author's direction. Although one of the world's most famous places and of key importance to understanding early Christianity, Nazareth has attracted little archaeological attention. Following a chance discovery in the 1880s, the site was initially explored by the nuns of the convent themselves - one of the earliest examples of a major programme of excavations initiated and directed by women - and then for decades by Henri Senès, whose excavations (like those of the nuns) have remained almost entirely unpublished. Their work revealed a complex sequence, elucidated and dated by twenty-first century study, beginning with a partly rock-cut Early Roman-period domestic building, Roman-period quarrying and burial, a well-preserved cave-church and major surface-level Byzantine and Crusader churches. The interpretation and broader implications of each phase of activity are discussed in the context of recent studies of Roman-period, Byzantine and later archaeology and contemporary archaeological theory, and their relationship to written accounts of Nazareth also assessed. The Sisters of Nazareth Convent provides a crucial archaeological study for those wishing to understand the archaeology of Nazareth and its place in Early Christianity and beyond"--